THE PRACTICE OF DRINKING FROM THE ”TEA“ GLASS IN IBARSKI KOLAŠIN (Heritage, 2022)
In this paper the author pays attention to the practice of drinking from big rakija, the so-called ”tea“ glass, distributed among the Serbs in Ibarski Kolašin. This act the author observes as an aspect of culture which Serbs from Ibarski Kolašin perceive as an element of their tradition, while the emphasis in the paper is on the subjective side of the researched phenomenon, what means that attention is focused on understanding the way in which its immediate bearers think and speak about it. The idea of the author, in other words, was to try to replace the classic ethnographic description of drinking from the ”tea“ glass, which would be given from the ”outside“, from the researcher’s point of view, with the approach in which the emphasis would be on personal descriptions of the mentioned practice, given from the point of view of its concrete bearers. The analytical procedure applied in achieving the set goal was based on an anthropologically key perspective, and that is the emic perspective, or view from the ”inside“, which means that, methodologically speaking, the author had used the qualitative approach, primarily the conversation with interlocutors. In this way, the author obtained the narrative material, which he transcribed, systematized, selected, and then transferred to the paper in an effort to present it in its original form, as it was noted in direct contact with interlocutors. The narrative material presented in the paper was obtained on the basis of field research conducted in Kosovska Mitrovica and Zubin Potok on several occasions during 2021 and 2022.
Keywords: drinking, drinking practice, big rakija glass, ”tea“ glass, narrative material, Serbs, Ibarski Kolašin, Kosovo and Metohija